Effect of repair parameters on composite plates under low velocity impact - Albayrak, Mustafa; Gür, Mustafa; Kaman, Mete Onur (My University, 2022)
In this study, the impact behavior of patch-repaired layered composite plates under low velocity impact loads was numerically investigated. For this purpose, layered composite plates with holes with different geometries in the middle were repaired with patches using various adhesives. Impact behavior of the composite material was investigated by dropping the strikers with different speeds on the repaired composite plate. Layered composite plate was used as the sheet and patch material, and the orientation angles are [0 ° / 45 ° / 45 ° / 0 °] for the plate and [0 ° / 45 °] for the patch. ANSYS Ls-Dyna finite element package program was used for three dimensional modelling and solution. Therefore, the effects of variables such as striker, adhesive, plate and patch on the impact behavior of layered composite material were investigated for different boundary conditions. It has been determined that the hexagonal patch type performs better than other patch geometries.
Keywords: Finite element method; Fiber reinforced composites; patch repair; low velocity impact